PENINGKATAN KEMAMPUAN PERKALIAN BILANGAN CACAH MELALUI PENDEKATAN PEMECAHAN MASALAH (Penelitian Tindakan Pada Siswa kelas IV SDN Guntur 04 Pagi Setiabudi Jakarta Selatan) - PERMATASARI, RINA (JURNAL PENDIDIKAN DASAR, 2012)
The aim of this research is to find out the effectivness of problem solving approach, to increase studentsâ mathematics ability of multiplication. This research was implemented at SDN Guntur 04 Pagi Setiabudi South Jakarta, with 44 students as subject of research. This is an action research by using Kemmis and McTaggart model in three cycles. Each cycle consists of planing, acting, observing, and reflecting. The data was collected through the studentsâ mathematic ability of multiplication by test, and non test observation of implementation the problem solving approach by sheet of observation to teacher and students activities, transcript of activities and document analysis, interviews and the documentation. The implication of researched indicates that the usage of problem solving approach can make students more active based on their mental ages development. Teacher can develop innovative method to suit the needs of sudents, so that learning becomes dynamic and meaningful.Keywords: problem solving approach, mathematics ability of multiplication, action research.